O pensamento combinatório de estudantes do 6º ano do ensino fundamental - NASCIMENTO, Ailton Gomes do (2022)
The teaching of mathematics, in the perspective of this research, goes beyond learning to apply formulas in problem situations. It is necessary to develop skills to refute results, question certain calculation procedures and relate different ways of solving a problem. Thus, the value of the correct answer gives way to the resolution process. In this sense, this research aims to propose mathematics activities for students in the 6th year of elementary school on combinatorial thinking to investigate the development of combinatorial reasoning and the concept of combination through personal strategies. The theoretical discussion that underlies the analyzes is based, mainly, on the studies of Hazzan; Borba, Aquino and others. The research took an exploratory qualitative approach and was developed in a public school in the municipal network of Benevides (PA) with students from the 6th year of elementary school during the mathematics classes of the workshops of the federal government project called Novo Mais Educação. The empirical material was built from the records of the resolutions of the proposed activities and this material was used in the analysis in an interpretative way. The research pointed out that the process of interpreting the strategies used by students to solve combinatorial problems allows the teacher to perceive the mathematical knowledge mobilized in the resolutions and, mainly, the understanding of the mathematical language.